Chlamydial screening of pregnant women in a sexually transmitted diseases clinic. Issue 5 (October 1982) - Goh, B T; Morgan-Capner, P; Lim, K S
Abstract : Fifty-three consecutive pregnant women seen over six months were screened for chlamydial infection, syphilis, gonorrhoea, trichomoniasis, and candidosis. Chlamydia trachomatis was isolated in 20 (37.7%) patients, of whom six were sexual partners of known cases of non-gonococcal urethritis (NGU) (two had associated gonorrhoea or candidosis) and six had gonorrhoea (three had associated trichomoniasis and candidosis). If treatment is given to contacts of NGU 14 patients with other presenting conditions would not have been treated unless chlamydial cultures had been performed. This may lead to potentially serious complications of chlamydial infection in both mothers and neonates.